Sub-wavelength grating for enhanced ring resonator biosensor - Flueckiger, Jonas; Schmidt, Shon; Donzella, Valentina; Sherwali, Ahmed; Ratner, Daniel M.; Chrostowski, Lukas; Cheung, Karen C. (Optics express, 2016)
While silicon photonic resonant cavities have been widely investigated for biosensing applications, enhancing their sensitivity and detection limit continues to be an area of active research. Here, we describe how to engineer the effective refractive index and mode profile of a silicon-on-insulator (SOI) waveguide using sub-wavelength gratings (SWG) and report on its observed performance as a biosensor. We designed a 30 μm diameter SWG ring resonator and fabricated it using Ebeam lithography. Its characterization resulted in a quality factor, Q, of 7 · 10 , bulk sensitivity Sb = 490 nm/RIU, and system limit of detection sLoD = 2 · 10 RIU. Finally we employ a model biological sandwich assay to demonstrate its utility for biosensing applications.